In vitro maturation and surrogacy in patients with vascular-type Ehlers–Danlos syndrome – A safe assisted reproductive technology approach. (June 2014) - Bergeron, Marie-Eve; Child, Tim; Fatum, Muhammad
Abstract Ehlers–Danlos syndrome (EDS) is an autosomal dominant connective tissue disorder with one of the highest maternal mortality rates of any condition. Patients with the vascular type of EDS are prone to spontaneous arterial and visceral ruptures. The occurrence of these severe and life-threatening complications is increased in pregnancy. Moreover, these patients carry a 50% risk of having an affected child. However, little is known about the risks of assisted conception treatments on these patients. We present the case of a 33-year-old woman suffering from EDS with a history of repeated ruptures of arterial aneurysms and a recently ruptured aneurysm of the splenic artery during her first intracytoplasmic sperm injection (ICSI) cycle who was then advised to undergo only unstimulated cycles. After a few natural ICSI cycles, the patient safely underwent two in vitro maturation cycles with pre-implantation genetic diagnosis in our unit. An unaffected blastocyst was transferred into a surrogate host. To our knowledge, this is the first case of EDS in assisted reproduction technologies including pre-implantation genetic diagnosis to be reported in the medical literature. This case has shown that unstimulated in vitro maturation and pre-implantation genetic diagnosis can safely be offered for vascular-type Ehlers–Danlos patients.